Evaluation of Scientific Sources in Mechanics Heiberg$1 (Bs Prolegomena to the Works of Archimedes and Hellinger$1 (Bs Encyclopedia Article on Continuum Mechanics /s - dell'Isola, Francesco; Eugster, Simon R.; Spagnuolo, Mario; Barchiesi, Emilio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book evaluates the importance of various historical sources and discusses their role in the creation and transmission of scientific knowledge. It presents an annotated translation of the introductory words given by Johan Ludvig Heiberg to his translation of the works of Archimedes. Further, it offers English translations of and commentaries on selected fundamental works by Ernst Hellinger and Gabrio Piola, which lay the groundwork for the modern theory of advanced materials, and also examines the criteria used to evaluate scientific works.
Part I. The loss and reconstruction of scientific sources with a particular reference to mechanics and theory of materials: The loss and reconstruction of the article by Hellinger in the Encyclopaedia of athematics -- The loss of the works by Archimedes and their reconstruction by Heiberg -- The loss of the works by Piola and the Italian tradition of Mechanics -- Part II. The recovery of the works by Hellinger, Archimedes, Piola and Heiberg: The monumental translation by Heiberg and his (nearly lost) commentaries written in Latin -- The masterpiece by Hellinger and its influences on modern continuum mechanics -- The forgotten Piola.-Part III. The recovery of the work by Archimedes and the role of Heiberg -- Part IV. The different ways of evaluating the importance of sources: why bibliometric indices?
Keywords: Mechanics, Applied; Solids; Technology; History; Science$1 (BHistory.s; Mechanics; Solid Mechanics; History of Technology; History of Science; Classical Mechanics; Mechanics -- History; Mechanics